2017
DOI: 10.1016/j.agee.2017.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Neonicotinoid insecticide removal by prairie strips in row-cropped watersheds with historical seed coating use

Abstract: A B S T R A C TNeonicotinoids are a widely used class of insecticides that are commonly applied as seed coatings for agricultural crops. Such neonicotinoid use may pose a risk to non-target insects, including pollinators and natural enemies of crop pests, and ecosystems. This study assessed neonicotinoid residues in groundwater, surface runoff water, soil, and native plants adjacent to corn and soybean crop fields with a history of being planted with neonicotinoid-treated seeds from 2008 to 2013. Data from six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 15 publications
4
24
0
1
Order By: Relevance
“…Deeper sources of water would likely be less contaminated as they are farther from surface sources of neonicotinoid contaminants [ 36 ]. Mean TMX detection from our survey of high-capacity irrigation wells in Wisconsin (0.28 μg/L) is within the range of previous reports of environmental detections of TMX near agricultural fields or in watersheds where these compounds are typically applied: a maximum TMX concentration of 0.032 μg/L from shallow groundwater and 0.376 μg/L from surface water runoff was reported from sites in Iowa where no seed treatments had been applied for two years [ 37 ]; maximum TMX concentrations of 0.46 μg/L from field-edge runoff and 0.16 μg/L from subsurface tile drains in agricultural fields were reported in Canada [ 38 ]; TMX detections up to 0.075 μg/L were reported from stream water in Ohio [ 15 ] and up to 0.185 μg/L in stream water in Iowa [ 16 ]; TMX concentrations up to 0.355 μg/L were reported from snowmelt in Canada [ 13 ]; and up to 1.49 μg/L was reported from wetlands adjacent to cultivated fields in Canada [ 5 ]. Previous work in central Wisconsin has also noted TMX detections up to 8.93 μg/L in shallow groundwater test wells and up to 0.580 μg/L from a small number of irrigation wells [ 2 ].…”
Section: Discussionsupporting
confidence: 82%
“…Deeper sources of water would likely be less contaminated as they are farther from surface sources of neonicotinoid contaminants [ 36 ]. Mean TMX detection from our survey of high-capacity irrigation wells in Wisconsin (0.28 μg/L) is within the range of previous reports of environmental detections of TMX near agricultural fields or in watersheds where these compounds are typically applied: a maximum TMX concentration of 0.032 μg/L from shallow groundwater and 0.376 μg/L from surface water runoff was reported from sites in Iowa where no seed treatments had been applied for two years [ 37 ]; maximum TMX concentrations of 0.46 μg/L from field-edge runoff and 0.16 μg/L from subsurface tile drains in agricultural fields were reported in Canada [ 38 ]; TMX detections up to 0.075 μg/L were reported from stream water in Ohio [ 15 ] and up to 0.185 μg/L in stream water in Iowa [ 16 ]; TMX concentrations up to 0.355 μg/L were reported from snowmelt in Canada [ 13 ]; and up to 1.49 μg/L was reported from wetlands adjacent to cultivated fields in Canada [ 5 ]. Previous work in central Wisconsin has also noted TMX detections up to 8.93 μg/L in shallow groundwater test wells and up to 0.580 μg/L from a small number of irrigation wells [ 2 ].…”
Section: Discussionsupporting
confidence: 82%
“…Several responses reported here differed slightly in terms of numeric outcome because here we included more complete datasets where available and used a consistent analytical framework across measures, incorporating a unique multidimensional summary achieved by calculating a scalar for each response. Companion studies have additionally established that prairie strips have the potential to improve soil quality (25), reduce nitrous oxide emissions losses from croplands through denitrification (29), and reduce exposure of beneficial insects to neonicotinoid insecticides (34). Collectively, our data indicate that, relative to other conservation options available to farmers and farmland owners, prairie strips may be a low-cost way (30) to address many major environmental problems associated with agriculture in the US Corn Belt, including soil erosion, emissions of nutrients and concomitant declines in water quality, and loss and degradation of habitat for native biota.…”
Section: Discussionmentioning
confidence: 99%
“…When plants are attacked by disease, plants often improve the coordination of SOD, POD and CAT to resist disease invasion, and this is the reason for increasing the three kinds of enzymes after inoculating H. maydis spores in the SST groups. Compared with CK, the contents of plant protective enzymes in maize leaves of the TSCA group were unchanged, which indicated that TSCA could not activate plant protective enzymes, but killed the pathogens by contact activity . The activity of plant protective enzymes of the ESCA group were obviously higher than that of the SST group, and it could be concluded that ESCA could induce resistance of maize by activating the enzymes.…”
Section: Resultsmentioning
confidence: 83%